Modification of the anatomical structure of the stem and leaves of rice, depending on the agro-ecological factors (Eurasian Journal of Ecology, 2016)
Agroecological factors (feeding area, dosage, timing and methods of mineral fertilizer dressing) make asignificant impact on the anatomical structure of rice organs ( stem, leaves, roots).
Keywords: Agroecological factors ( feeding area; dosage; timing and methods of mineral fertilizer dressing); rice; anatomical structure of stem; leaves; roots.